2016
DOI: 10.1038/ejhg.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-related receptor gamma implicated in a phenotype including hearing loss and mild developmental delay

Abstract: Analysis of chromosomal rearrangements has been highly successful in identifying genes involved in many congenital abnormalities including hearing loss. Herein, we report a subject, designated DGAP242, with congenital hearing loss (HL) and a de novo balanced translocation 46,XX,t(1;5)(q32;q15)dn. Using multiple next-generation sequencing techniques, we obtained high resolution of the breakpoints. This revealed disruption of the orphan receptor ESRRG on chromosome 1, which is differentially expressed in inner e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…More recently Schilit et al (2016) demonstrated that a translocation between chromosomes 1 and 5 that disrupts the ESRRG gene is strongly implicated as the cause of congenital hearing loss and mild developmental delay in a young female patient (Schilit et al, 2016).…”
Section: Nonclassical Estrogen-related Receptors (Errs) In the Cochleamentioning
confidence: 99%
“…More recently Schilit et al (2016) demonstrated that a translocation between chromosomes 1 and 5 that disrupts the ESRRG gene is strongly implicated as the cause of congenital hearing loss and mild developmental delay in a young female patient (Schilit et al, 2016).…”
Section: Nonclassical Estrogen-related Receptors (Errs) In the Cochleamentioning
confidence: 99%
“…ESRRG also plays a key role in vascular calcification [117] and is involved in the determination of bone density in women [118]. It crosstalks with ATF6a to coordinate ER stress response [119] and is implicated in hearing loss and mild developmental delays [120]. ESSRG is highly expressed in the nervous system of mice embryos [121], and mice lacking neuronal ESSRG in the cerebral cortex and hippocampus exhibit defects in spatial learning and memory [122].…”
Section: Transcriptional Regulation Of Grinamentioning
confidence: 99%
“…Six genes (SH2D5, KIAA0825, LSAMP, KLHL29, PHLDB1 and KNTC1) were not annotated in any known GO term and KEGG functional classification. Most genes, such as KNTC1 (Liu et al, ), PHLDB1 (Baskin et al, ) and SH2D5 (Zheng et al, ), are involved in the development of various tumour cells, neural behaviour (like LSAMP) (Singh et al, ) and sensory ability defects (Schilit et al, ). However, KLHL29 has known functions in the protein degradation process through the ubiquitination pathway, and this gene was also identified as having a heat stress association in catfish (Jin et al, ; Liu et al, ).…”
Section: Resultsmentioning
confidence: 99%